KINERJA PEGAWAI PADA DINAS PENDIDIKAN PEMUDA DAN OLAHRAGA KOTA PARIAMAN - NIDYA SHELVIE (Jurnal Bahana Manajemen Pendidikan, 2016)
This research is aimed to know  about employee performance. This is a descriptive research with a population 43 people. The research instrument was questionnaire in the form of Likert Scale, which has proven its validity and reliability. Research data processing performed by using the average formula. In general, the result of the research is employee performance is good with an average score 4,19